The reform of criminal justice in France: the problem of the balance between the formalism of fundamental rights and efficiency - Danelciuc-Colodrovschi, Nataşa (Journal of the Belarusian State University. Law, 2021)
This article aims to study the recent reforms that have been implemented in France in order to remedy the systemic problems the justice system is facing and to fight effectively against criminality. Even if considered necessary, these reforms are strongly criticised because they would be more focused on managerial questions of cost control, efficiency, work performance than that of the official objectives declared by the government and, especially, the respect of fundamental rights. The study of the key points of the introduced changes shows that the criticisms are not completely unfounded and highlights the role of the constitutional judges in maintaining the fragile balances between cultural heritage, the search for performance and ensuring both security and the rule of law.